Farewell lecture by Professor A. M. Celâl Şengör the developments in geology during the last 40 years I spent at the ITU and ITU's contribution - Şengör, A.m. Celal (Bulletin of the Mineral Research and Exploration, 2022)
This paper is a somewhat enlarged version of my farewell lecture delivered on 23rd March 2022 at the Faculty of Mines of the Istanbul Technical University (ITU). It reviews some of the important developments in geology during the 40 years I was a faculty member at the ITU and the contribution of the ITU geologists to some of these developments. As stipulated in the syllabus, the first hour-and-a half of this lesson we devoted to a discussion of normal faults. As this is my last lesson as a faculty member at the ITU because of the compulsory retirement imposed by law on every professor at age 67 in Türkiye, I gladly respond to a general request that I review in the remaining hour-and-a-half the development of geology in the world during the 40 years I spent at the ITU and ITU's contribution to some of these developments.